2023
DOI: 10.3390/polym15153289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Correlation Analysis of the Rheological Properties of Ground Tire Rubber and Styrene Butadiene Styrene Compound-Modified Asphalt

Abstract: With the increase in highway traffic volume, many waste tires are being produced, which puts serious pressure on the global ecological environment. Processing waste tires into powder and adding them to asphalt is an important and effective way to solve this noticeable environmental challenge. In this paper, to produce ground tire rubber (GTR) and styrene-butadiene-styrene (SBS) compound-modified asphalt, GTR was put into SBS-modified asphalt (GTRSA). Subsequently, some ordinary property tests, frequency sweep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…SBS modification enhances the rheological properties of asphalt binders, resulting in increased stiffness and elasticity, which are crucial for maintaining pavement performance under varying environmental conditions and traffic loads [ 6 , 7 ]. Studies have shown that SBS-modified mixtures possess improved fatigue resistance due to the polymer’s ability to enhance flexibility and tensile strength, thereby reducing crack initiation and propagation [ 8 , 9 ]. Furthermore, SBS modification greatly increases the binder’s high-temperature efficiency, which is crucial for preventing rut development under heavy traffic, hence improving rutting resistance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…SBS modification enhances the rheological properties of asphalt binders, resulting in increased stiffness and elasticity, which are crucial for maintaining pavement performance under varying environmental conditions and traffic loads [ 6 , 7 ]. Studies have shown that SBS-modified mixtures possess improved fatigue resistance due to the polymer’s ability to enhance flexibility and tensile strength, thereby reducing crack initiation and propagation [ 8 , 9 ]. Furthermore, SBS modification greatly increases the binder’s high-temperature efficiency, which is crucial for preventing rut development under heavy traffic, hence improving rutting resistance [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent research in the field of SBS (styrene-butadiene-styrene) polymer-modified asphalt has seen significant advancements aimed at enhancing the performance and durability of asphalt materials [21][22][23]. These studies have focused on various aspects, including the selection of optimal SBS modifiers to improve elasticity and adhesion [24], the development of innovative polymer-modified asphalt binders [25], and the exploration of novel applications in construction and pavement engineering [20,26].…”
Section: Introductionmentioning
confidence: 99%